Abnormal Return: Right Issue, Stock Split, Mergers and Acquisitions (Empirical Study of Companies Listed on the Indonesia Stock Exchange For the Period 2020-2023) - Riski, Muhammad; Satrya Wibowo, Agus; Yuniati, Ade; Ichsan Diarsyad, Muhammad; Muhammad Ari, Tommy (DINASTI RESEARCH, 2025)
This research examines the significant differences in abnormal return at the time of the announcements of right issues, stock splits, and mergers & acquisitions. The research was conducted on companies listed on the Indonesia Stock Exchange from 2020 to 2023. The independent variables used in this study are right issues, stock splits, and mergers & acquisitions. The dependent variable in this research is abnormal return. This study employs the market model method during corporate actions with an event window observation of 20 days before and 20 days after the announcements of right issues, stock splits, and mergers & acquisitions. The data used in this study includes closing stock prices and the Composite Stock Price Index. The results of this study indicate that there are no significant differences in abnormal return at the time of right issues, stock splits and mergers & acquisitions.